Penggunaan Kontrasepsi Hormonal Berisiko Kanker Payudara: A Literatur Review - Norna Amalia Sholeha; Herin Mawarti; Masruroh (Indonesian Health Science Journal, 2025)
Introduction: Breast cancer is one of the most common types of cancer found in women worldwide. Risk factors for breast cancer vary, including genetic, environmental, and lifestyle factors. One factor that has received attention is the use of hormonal contraception. Purpose: This literature review aims to review the Use of Hormonal Contraception Risk of Breast Cancer. Methods: Initial literature was obtained from 11 international and national articles such as Google Scholar, Science Direct, and Pubmed with the keys Hormonal contraception, Risk, Breast Cancer. The next stage is to conduct a selection by considering the year of publication (2019-2024). With full text. Furthermore, articles that are considered less relevant are removed. Data are compiled, summarized and displayed in table form based on several themes. Results: The reviewed studies were 11 that discussed the use of hormonal contraception on the occurrence of Breast Cancer.